Culture, creativity and economy collaborative practices, value creation and spaces of creativity - Hracs, Brian J.; Brydges, Taylor; Haisch, Tina editor; Hauge, Atle; Jansson, Johan; Sjöholm, Jenny (Routledge, 2022)
This book nuances our understanding of the contemporary creative economy by engaging with a set of three key tensions which emerged over the course of eight European Colloquiums on Culture, Creativity and Economy (CCE): 1) The tension between individual and collaborative creative practices, 2) The tension between tradition and innovation, and 3) The tension between isolated and interconnected spaces of creativity. This book will be of interest to students, scholars and professionals researching the creative economy, as well as specific cultural and creative industries, across the humanities and social sciences"--